2022
DOI: 10.3390/genes13040698
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Analysis of the L-2-Hydroxyglutarate Dehydrogenase Gene Mutations and Their Biological Impact on Disease Etiology

Abstract: The L-2-hydroxyglutarate dehydrogenase (L2HGDH) gene encodes an important mitochondrial enzyme. However, its altered activity results in excessive levels of L-2-hydroxyglutarate, which results in diverse psychiatric features of intellectual disability. In the current study, we executed an in-silico analysis of all reported L2HGDH missense and nonsense variants in order to investigate their biological significance. Among the superimposed 3D models, the highest similarity index for a wild-type structure was show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…L2HGA gene (14q22.1) encodes a putative mitochondrial protein with homology to flavin adenine dinucleotide (FAD) dependent oxidoreductases. So far, the human gene mutation database has reported 52 missense or nonsense mutations implicated in the reduced action of the L2HGDH enzyme [13][14][15]. The genetic variant detected in our patient is a missense mutation leading to a substitution of a threonine by a isoleucine in position 190 of the encoded protein (p.Thr190Ile) lying in the highly conserved FAD-binding domain, disturbing the enzymatic function.…”
Section: Discussionmentioning
confidence: 79%
“…L2HGA gene (14q22.1) encodes a putative mitochondrial protein with homology to flavin adenine dinucleotide (FAD) dependent oxidoreductases. So far, the human gene mutation database has reported 52 missense or nonsense mutations implicated in the reduced action of the L2HGDH enzyme [13][14][15]. The genetic variant detected in our patient is a missense mutation leading to a substitution of a threonine by a isoleucine in position 190 of the encoded protein (p.Thr190Ile) lying in the highly conserved FAD-binding domain, disturbing the enzymatic function.…”
Section: Discussionmentioning
confidence: 79%
“…Deficient activity of hs L2HGDH can lead to l -2-HG accumulation, which has been suggested to be the cause of l -2-HGA. So far, 36 missense mutations and 13 truncating mutations of hs L2HGDH have been identified in l -2-HGA patients ( 55 , 56 ). Truncating mutations usually lead to the absence or the loss of function of the protein and thus are classified as pathogenic.…”
Section: Resultsmentioning
confidence: 99%
“…This article contains supporting information ( 37 , 53 , 55 , 58 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ).…”
Section: Supporting Informationmentioning
confidence: 99%
“…This gene provides L-2-hydroxyglutarate dehydrogenase, a mitochondrial enzyme involved in the conversion of L-2hydroxyglutarate to 2-ketoglutarate. 63 Studies in mice have shown that a defective form of L-2-hydroxyglutarate dehydrogenase leads to white matter abnormalities, neuroinflammation, improper neurogenesis of the hippocampal region, and neurodegeneration. 64 Mutations in this gene cause L-2-hydroxyglutaric aciduria, characterized by ID, cerebellar ataxia, epilepsy, speech problems, and an increased amount of L-2-hydroxyglutaric acid in urine, blood, and cerebrospinal fluid.…”
Section: L-2-hydroxyglutarate Dehydrogenase; L2hgdhmentioning
confidence: 99%
“…64 Mutations in this gene cause L-2-hydroxyglutaric aciduria, characterized by ID, cerebellar ataxia, epilepsy, speech problems, and an increased amount of L-2-hydroxyglutaric acid in urine, blood, and cerebrospinal fluid. 63 Lines Homolog 1; LINS1…”
Section: L-2-hydroxyglutarate Dehydrogenase; L2hgdhmentioning
confidence: 99%